SpUSP, an annexin-interacting universal stress protein, enhances drought tolerance in tomato - Loukehaich, Rachid (Journal of experimental botany, 2012)
Universal stress protein (USP) appears to play an active role in the abiotic stress response, but their functions remain largely unknown in plants. A USP gene (SpUSP) was cloned from wild tomato (Solanum pennellii) and functionally characterized in cultivated tomato in the present study. The SpUSP transcript is abundantly accumulated in leaf stomata and its expression varied with the circadian rhythm. SpUSP was remarkably induced by dehydration, salt stress, oxidative stress, and the phytohormone abscisic acid (ABA) etc. This protein was predominantly localized in the nucleus and cell membrane. Overexpressing SpUSP increased drought tolerance of tomato in the seedling and adult stages. Under drought stress, the ABA content significantly increased in the SpUSP-overexpressing plants, which induced stomatal closure and reduced water loss, leading to the enhancement of drought tolerance. Based on the microarray data, a large number of chlorophyll a/b-binding proteins and photosystem-related genes were up-regulated in the SpUSP-overexpressing plants under drought conditions, which possibly enhanced the stomatal sensivitity to ABA and maintained the photosynthetic function. SpUSP overexpression also alleviated the oxidative damage accompanied by oxidative stress-responsive gene activation and osmolyte accumulation. Annexin (SGN-U314161) was found to interacte with SpUSP in the yeast two-hybrid method. This interaction was further confirmed by the bimolecular fluorescence complementation assay. The present study demonstrated that the annexin-interacting SpUSP plays important roles in the drought tolerance of tomato by influencing ABA-induced stomatal movement, increasing photosynthesis, and alleviating oxidative stress